EXPERIENCE-BASED PERCEPTION OF RESEARCH LITERACY DEVELOPMENT BY ENGLISH UNDERGRADUATES IN CHINA - Cheng, Yixin (PUPIL: International Journal of Teaching, Education and Learning, 2018)
In the sagging world economy, innovation has been promoted to an unprecedented position. China is especially desirous of innovation to facilitate her realization of the China Dream. But the stereotyped Chinese undergraduates are poignantly criticized for their poor research literacy, especially English undergraduates who demonstrate poor initiatives in graduation thesis writing. The researcher, as a teacher for English majors in China, has long noticed the contradiction between the glamorous national prospects and the disappointing undergraduates’ performance. She has integrated course paper writing in the research-oriented class, so as to arouse English majors’ awareness of research and pave the way to research literacy development. The three-year longitudinal action research has been conducted by the teacher’ raptly supervising the paper-writing process in addition to the subject knowledge study, in the hope of finding English majors’ perception of their research literacy and the factors that help develop their research literacy. This research has also been aided with data from class observation, questionnaires and focuses interviews, in an effort to further the previous philosophical discussion, and to suggest properly converting from the traditional cramming classes to research-oriented class in China.